PENGGUNAAN MEDIA BOTOL CERDAS BERBANTUAN TALKING STICK TERHADAP HASIL BELAJAR KEMAMPUAN BERBICARA SISWA KELAS IV SD NEGERI PAO-PAO KABUPATEN GOWA - Kamelia Marsanda Muslim; Abd. Munir Kondongan; Maria Ulviani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of using smart bottle media assisted by the talking stick method on the speaking ability of fourth-grade students at SD Negeri Pao-Pao. This research employed a quantitative approach with a pre-experimental design using the One Group Pretest–Posttest model, involving 28 students as the research sample. Data were collected through speaking ability tests administered before and after the treatment (pre-test and post-test) and were analyzed using descriptive and inferential statistical techniques. The results showed that the use of smart bottle media assisted by the talking stick method improved students’ speaking ability, as indicated by the increase in the mean score from 48.41 in the pre-test (low category) to 86.14 in the post-test (high category). Furthermore, the results of the Wilcoxon Signed Ranks Test showed a significance value of 0.000 < 0.05, indicating a statistically significant difference between the pre-test and post-test scores. Therefore, it can be concluded that the use of smart bottle media assisted by the talking stick method has a significant effect on improving the speaking ability of fourth-grade students at SD Negeri Pao-Pao.